TASKS AND PROSPECTS OF FORMING A “SANE SOCIETY” IN ERICH FROMM'S SOCIAL-EXISTENTIAL CONCEPT (Scientific journal of the Fergana State University, 2026)
The tasks and prospects of forming a “sane society” in Erich Fromm's socio-existential concept, and the work “Sane Society” analyzes the dehumanization (dehumanization) of society under the influence of destructive social conditions.